Evolutionary transformation into transhuman and posthuman in selected 21st century science fiction novels - Mirenayat, Sayyed Ali (2018)
We now live in a world filled to capacity with advancing technologies which have massive impacts on our lives and causes us to become dependent on them day by day. Science Fiction, as a literary genre, has always gone with in tandem with technological advances hand in hand. A movement called transhumanism exists which aims to make humans immortal and transform them into less vulnerable living machines. Two significant concepts in this movement are transhuman and posthuman which are applied as conceptual frameworks in this study to analyse the technological transformation of humans in four selected 21st century Science Fiction novels, namely Mindscan (2005) by Robert J. Sawyer (b.1960), Machine Man (2011) by Max Barry (b.1973), Amped (2012) by Daniel H. Wilson (b.1978), and The Transhumanist Wager (2013) by Zoltan Istvan (b.1973). As for the relationship between these two concepts, transhuman is defined in this study as a modified form of human by which new human is still biological, but enhanced and mostly focuses on changing the abilities of current human to eradicate diseases and stop death; meanwhile, posthuman is defined as when a new being is a less or non-biological form which is extremely enhanced and merged with advanced technology, but cannot be considered human anymore. It mainly centers on going far beyond transhuman and step into a nonhuman status in which the biology is obsolete. This study also aims, to examine the futurist authors’ depictions of transformation of selected characters into transhuman and posthuman and their influences in society, to explore the views of democratic transhumanism by James Hughes and unwelcome perfection by Sydney Perkowitz in the transhuman era and also the notions of weaponisation by Daniel Dinello, mechanical slave by Despina Kakoudaki and new vulnerability by Mark Coeckelbergh in the posthuman era, and to discover the authors’ portrayals of selected characters’ transformation into new beings or products. Within the framework, the analyses investigate how and why the meanings of human are changed after merging with technology through new products in which their original identities and humanness are lost. As such, this study examines the potential changes in characters’ minds, bodies, and behaviors after the process of transformation. More specifically, Jethro Knights in The Transhumanist Wager becomes an authoritarian transhuman called Omnipotender, Owen Gray in Amped turns into an alienated transhuman with an unwelcome enhancement called Zenith, Charles Neumann in Machine Man transforms into an obedient and weaponised cyborg slave with a discarded body called Cyber Ghost, and Jake Sullivan and Karen Bessarian in Mindscan turns into vulnerable androids with man/machine duality called Philosophical Zombie. All in all, the contribution of this study is to highlight the various understandings of the concepts of transhuman and posthuman in order to shed light on selected characters’ transformations in the selected Science Fiction novels, and also to show how the selected writers illuminate the concepts and the related notions in the selected fictions. Findings from this study suggest that character transformation can further be analysed in the light of sub-human and nonhuman transformation in other 21st century Science Fiction novels. Moreover, focusing on the selected texts in the light of singularity, aesthetics, and ethics would strongly introduce new readings for further studies.